Band patterns seen by electron microscopy in ordered arrays of bovine and human fibrinogen and fibrin after negative staining. - Williams, R C (1983)
When fibers of fibrin clots or fragments of fibrinogen pellets are negatively stained they exhibit in the electron microscope characteristic patterns of cross-striations or bands. Those found in pellet material are indistinguishable from those seen in thrombin-induced fibrin fibers. The pattern seen in fibrin from bovine sources contains three equally spaced faint bands between every two of the broad prominent ones, spaced 23 nm apart. Human material shows a different pattern, one wherein no central faint band is seen, whereas the two remaining ones are broader. Its character is unaffected by crosslinking following fiber formation and preceding negative staining. The bovine pattern, however, is converted by such crosslinking to one that closely resembles the human. It is suggested that the striation pattern in human fibrin is due to juxtapositions of E domains of the parallel-aligned fibrin monomers with tightly coiled COOH-terminal regions of beta and gamma polypeptide chains, with no discernible contribution to the pattern from the alpha chain. In negatively stained untreated fibers of bovine fibrin, however, it is proposed that the COOH-terminal region of the alpha chain becomes tightly coiled, thereby contributing the faint central striation to the band pattern. Crosslinking prevents this conformational change in the alpha chain.